Firn temperature-time series to 25 meter depth at two sites along the west Expéditions Glaciologiques Internationales au Groenland (EGIG) line, Greenland 2022-2023 ... - Harper, Joel; Humphrey, Neil (NSF Arctic Data Center, 2024)
This archive contains firn temperature data collected at two sites in the western Greenland Ice Sheet percolation zone. The sites are located along a lower elevation transect of the Expéditions Glaciologiques Internationales au Groenland (EGIG) line. The data are time series of firn temperature measured in boreholes drilled to 15 or 25 meter depth. The boreholes were drilled by firn coring methods after which the sensor strings were installed, and the holes were backfilled with fine sifted snow. These measurements are associated with additional datasets collected as part of a NSF Arctic Observing Network project and include measurements at multiple sites on the EGIG line of firn temperature and firn density/ice content. ...